"It makes me sad": Archival Pedagogy in a Time of Covid‐19. Issue 1 (13th October 2021) - Poole, Alex H.; Zhang, Jane
Abstract: Despite COVID‐19's devastating repercussions on higher education, scholars have yet to address its impact on Library and Information Science pedagogy. This exploratory qualitative case study centers on how archival educators weathered the onslaught of the pandemic. Drawing upon semistructured interviews with 31 archival educators and documentary evidence, this research addresses the sudden shift to online education; the concomitant loss of hands‐on work opportunities and the workarounds educators developed; affectivity and an emergent ethics of pedagogical care among students and educators; and educators' lessons learned from the pandemic and their future projections regarding archival education. This paper illuminates the evolving landscape of pedagogy and its attendant challenges preparing the next generation of archival professionals during an unprecedented period of duress.